Authors' Reply to Torpedo Retinopathy or Chorioretinopathy? - Ramesh Venkatesh; Kushagra Jain; Arpitha Pereira; MB Thirumalesh; Naresh Kumar Yadav (Journal of Ophthalmic & Vision Research)
Abstract ssss